Implementation of a four probes measuring system to determine the resistivity of thin films with temperature dependence - Salas Casapino, Carlos Alberto (2017)
Resistivity measurements in thin film samples depending on the temperature and on the lm thickness is always a subject of interest, above all when it comes to new materials. This work presents the implementation of a measuring system for thin fi lm resistivity based on four probes showing the dependency of the resistivity on the temperature as well as on the film thickness. In order to change the temperature of the samples, a heat source based on a Peltier element was implemented into the measuring system. A Graphical User Interface using a LabVIEW software controls all the devices of the measuring system and allows the user to calculate the thin lm resistivity choosing between four measuring method: Van der Pauw, Modi ed Van der Pauw, Linear Van der Pauw and Linear Four Probes methods. Resistivity in aluminum and tungsten thin lm samples with 100, 300, and 600 nm thickness were measured at temperatures between 303K and 373K with increments of 5 K. The results obtained are higher than bulk resistivity values and agrees with the present theory. Moreover, it is shown that the resistivity values obtained and its corresponding temperature coeficients increases as the film thickness decreases.